2019
DOI: 10.24106/kefdergi.2893
|View full text |Cite
|
Sign up to set email alerts
|

İlkokullarda Okuma Güçlüğünü Sağaltmaya Yönelik Kullanılan Öğretimsel Düzenlemelere İlişkin Öğretmen Görüşleri

Abstract: İlkokul 1. ve 2. sınıflarda ilkokuma yazma öğretiminde gözlenen sorunların başında okuma güçlüğü gelmektedir. Öğretmenlerin okuma güçlüğüne ilişkin algılarının ve okuma güçlüğüne yönelik çözüm önerilerinin belirlenmesi önem arz etmektedir. Bu kapsamda çalışmanın amacı öğretmenlerin okuma güçlüğüne ilişkin algılarının farklı değişkenlere göre belirlenmesidir. Çalışma Denizli Merkez ve ilçelerinde görev yapmakta olan 359 sınıf öğretmeni ile gerçekleştirilmiştir. Karma araştırma yöntemi ile yapılandırılan araştır… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 44 publications
(35 reference statements)
0
1
0
1
Order By: Relevance
“…Doğan (2013) found that the teachers did not have this information at a sufficient level in his research on the level of knowledge of primary school and Turkish teachers about reading disabilities and the level of identifying students with reading disabilities. It has been determined that primary school teachers have theoretical knowledge about reading disability, but their knowledge level is not sufficient in identifying students with reading disability and in the methods-techniques to be used for these students (Yurdakul, 2014;Yurdakul & Kırmızı, 2019). Similarly, in another study, although pre-service primary school teachers have knowledge about reading and math disabilities, they feel inadequate in identifying students with reading disabilities and overcoming these disabilities (Kuruyer et al, 2019).…”
Section: Deficiencymentioning
confidence: 99%
“…Doğan (2013) found that the teachers did not have this information at a sufficient level in his research on the level of knowledge of primary school and Turkish teachers about reading disabilities and the level of identifying students with reading disabilities. It has been determined that primary school teachers have theoretical knowledge about reading disability, but their knowledge level is not sufficient in identifying students with reading disability and in the methods-techniques to be used for these students (Yurdakul, 2014;Yurdakul & Kırmızı, 2019). Similarly, in another study, although pre-service primary school teachers have knowledge about reading and math disabilities, they feel inadequate in identifying students with reading disabilities and overcoming these disabilities (Kuruyer et al, 2019).…”
Section: Deficiencymentioning
confidence: 99%
“…Öğretmenler ile yapılan araştırmalarda; öğretmenler; okuma güçlüğü çeken öğrencileri belirleyebilme ve bu öğrenciler için yapılması gerekenler konusunda kendilerini tam olarak yeterli görmediklerini belirtmişlerdir (Doğan, 2013;Altun, Ekiz ve Odabaşı, 2011). Yurdakal ve Susar Kırmızı (2019), öğretmenlerin genel olarak okuma güçlüğüne ilişkin teorik bilgilerinin olduğunu, ancak hangi yöntem-teknik ve stratejinin kullanılması gerektiğini bilmediklerini belirtmektedir.…”
unclassified